1989
DOI: 10.1210/mend-3-1-44
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Estrogen Induction of Two Estrogen Receptors (ER) Messenger Ribonucleic Acids in the Rainbow Trout Liver: Sequence Homology with other ERs

Abstract: The estrogen-binding region of the cDNA for chicken ER reveals a mRNA of 3.5 kilobases (kb) in rainbow trout liver. The level of this messenger, which is very low in the liver of naive male animals, can be increased by estrogen stimulation. With this chicken probe, we have isolated a clone from a lambda gt10 trout liver cDNA library. The partial cDNA sequence, which encompasses most of the coding region, shows two domains of striking amino acid homology with human, avian, and Xenopus estrogen receptors (ERs) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(79 citation statements)
references
References 29 publications
3
76
0
Order By: Relevance
“…The rtER cDNA insert (Pakdel et al, 1989) and the Vg cDNA insert (Le were labelled with the random primer labelling kit (Amersham), in the presence of [ cr-32P]dCTP ( -800 Ci/mmol).…”
Section: Labelling Of Cdna Probementioning
confidence: 99%
“…The rtER cDNA insert (Pakdel et al, 1989) and the Vg cDNA insert (Le were labelled with the random primer labelling kit (Amersham), in the presence of [ cr-32P]dCTP ( -800 Ci/mmol).…”
Section: Labelling Of Cdna Probementioning
confidence: 99%
“…Hybridization was performed under high stringency conditions (Thomas, 1980) using rainbow trout PRL cDNA . The nylon membrane (BiodynPall) was then stripped and reprobed for p-actin mRNA using rainbow trout cDNA (Pakdel et al, 1989). The autoradiographs were quantified by densitometric scanning.…”
Section: Prl Mrh!a Measurementmentioning
confidence: 99%
“…Hybridization was performed with a 32P-labeled complete rtER cDNA under Thomas' conditions (1980). Trout pro-opiomelanocortin (POMC) ) and rtER (Pakdel et al, 1989) cDNAs were cloned in our laboratory. Full-length rtER cDNA as well as two different restriction fragments, PstI-PstI encoding the C and D domains and ApaI-Apal encoding E domain of rtER, were used in hybridization experiments.…”
Section: Northern Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…From the work of Saceda et al (57), it appears that estradiol (E2) can upregulate the ER gene activity in MCF-7 cells, but the DNA sequences mediating this effect are still unknown. In several oviparous species and in rat, such an autoregulation has been shown in liver cells, where estrogen exert a positive control on ER mRNA and/or protein levels (48,49,61,65). We have recently demonstrated that in rainbow trout, upregulation is mediated by two distinct mechanisms: estrogen induces both a stabilization of the rainbow trout ER (rtER) mRNA and an increase in the rtER gene Cell culture and transient transfection.…”
mentioning
confidence: 99%